Old Discipline, New Trajectories: Theories, Methods and Practices in Anthropology - de Munck, Victor C.; Garalytė, Kristina (Vilnius University Proceedings, 2022)
Going under the title “Old Discipline, New Trajectories: Theories, Methods and Practices in Anthropology”, the conference seeks to provide a “home” for socio-cultural and linguistic anthropologists as well as archeologists and bio-evolutionary anthropologists who identify themselves and seek to connect with scientifically minded anthropologists. It does not neglect the humanistic aspect of anthropology and embraces it as part of the unity implicit in the study of human lifeways and the cultural stuff that gives meaning, direction and collective identities to us. The conference might be seen as an important foundational step to establishing closer collaboration and integration among different disciplinary and methodological strands within the discipline of anthropology. The conference will broadly focus on theory, methods and practices in anthropology and will address the following questions:-  Can we still say that anthropology is the most scientific of humanities and most humanistic of social sciences?-  What does a scientific approach to the study of culture imply theoretically and methodologically?-  Should ethnography still hold a central place in anthropology?-  How can the results of the study of human evolution, cultural evolution and language evolution contribute insights into the current human condition?-  What are the consequences the current rapid technological change is having on culture?-  What can anthropology contribute to the important questions of today’s world such as pandemics, growing economic inequality, fascism, second demographic transition, climate change, etc.?